ENVIRONMENTAL CONCERN DAN HEALTH CONSCIOUSNESS TERHADAP MINAT BELI SENSATIA BOTANICALS - Alyssa Nadira Salsabila Suy (2021)
This research is a descriptive quantitative study that was conducted with the aim of knowing, analyzing and proving the influence between environmental concern and health consciousness with the purchase intention of Sensatia Botanicals' green skincare product. The data analysisptechnique. used is descriptivecandginferential analysis technique using software SmartPLS and Microsoft Office Excel. The sampling was carried out using the Malhotra formula with the calculation results of 55 respondents. Based on the test results data, the results obtained are (1) Environmental Concern and Health Consciousness variables have a contribution of 44.1% to Purchase Intention while the remaining 55.9% comes from the influence of other variables. (2) Environmental Concern has a.positive and significant.effect on Purchase Intention by 68.8%, (3) Health Consciousness has no positive and.significant effect on Purchase Intention.